A Digital-Based Flipped Classroom Strategy for Enhancing Students' Mathematical Representation Ability - Tanjung, Meylia Hapni; Reflina, Reflina (Universitas Islam Negeri Raden Intan Lampung, 2026)
Students' mathematical representation ability remains one of the fundamental competencies that is often underdeveloped in mathematics learning, particularly in topics requiring abstract reasoning such as trigonometric functions. Although the Flipped Classroom approach has been widely implemented, empirical evidence regarding its effectiveness in improving mathematical representation ability in Indonesian secondary education is still limited. This study aimed to examine the effectiveness of a Flipped Classroom strategy in enhancing students' mathematical representation ability. A quasi-experimental design with a pretest–posttest control group was employed involving 65 eleventh-grade students from a public senior high school in Indonesia, consisting of 32 students in the experimental group and 33 students in the control group. The experimental group received instruction through the Flipped Classroom strategy, whereas the control group was taught using conventional instruction. Data were collected using a mathematical representation ability test and analyzed through descriptive statistics, normality and homogeneity tests, and an independent samples t-test. The findings revealed that both groups had comparable initial abilities; however, the experimental group achieved a significantly higher posttest mean score (81.75) than the control group (70.24). Statistical analysis confirmed a significant difference between the two groups (t = 12.67, p < .001), indicating that the Flipped Classroom strategy effectively improved students' mathematical representation ability. These findings contribute to the growing evidence supporting student-centered, technology-enhanced learning environments for mathematics education and suggest that the Flipped Classroom can be adopted as an effective instructional strategy to foster mathematical representation skills in secondary schools.